Diagnostic options of non-invasive assessment of fibrosis at diffuse liver diseases - I. Yu. Pirogova; S. A. Pyshkin; Ye. V. Yefremova; A. N. Gorfinkel; S. G. Pogorelova; N. V. Abramovskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study potentials of noninvasive methods application for assessment of liver fibrosis at screening diagnosis of patients with diffuse liver diseases.Material and methods. Overall 188 HCV RNApositive patients and 61 HBV DNA-positive were investigated. The stage of disease in all patients was verified by morphological study with assessment of histological activity index (HAI) and stage of fibrosis (F). These data were compared to data of non-invasive evaluation of liver fibrosis – i.e. results of biochemical tests (de Ritis coefficients, APRI), ultrasound investigation with Doppler ultrasonography, videodensitometry, elastometry (EM) by FibroScan device («EchoSens», France).Results. Significant differences in scores of liver tissue elasticity in relation to stage of fibrosis (F0, F1, F2, F3, F4) – р<0,001 were revealed at HCV-infection and р><0,05 at HBV-infection. EM sensitivity and specificity ranged from 0,8 to 0,99 (area under the ROC-curve). Canonical discriminant analysis with drawing of territorial map, that allow to define fibrosis stage as mild, moderate or severe, using data of ultrasound investigation, was carried out. Conclusions. Application of non-invasive methods of evaluation of fibrosis is reasonable at primary investigation of HCV RNA-and HBV DNA-positive patients. Today high diagnostic accuracy allows to consider elastometry as a method of choice in diagnostics of liver fibrosis in diffuse liver diseases. ><0,001 were revealed at HCV-infection and р< 0,05 at HBV-infection. EM sensitivity and specificity ranged from 0,8 to 0,99 (area under the ROC-curve). Canonical discriminant analysis with drawing of territorial map, that allow to define fibrosis stage as mild, moderate or severe, using data of ultrasound investigation, was carried out.Conclusions. Application of non-invasive methods of evaluation of fibrosis is reasonable at primary investigation of HCV RNA-and HBV DNA-positive patients. Today high diagnostic accuracy allows to consider elastometry as a method of choice in diagnostics of liver fibrosis in diffuse liver diseases.